Hybrid solar cells using PbS nanoparticles - Gunes, Serap; Fritz, Karolina P.; Neugebauer, Helmut; Sariciftci, Niyazi Serdar; Kumar, Sandeep; Scholes, Gregory D. (ELSEVIER SCIENCE BV, 2007)
Solution-processed bilayer heterojunction hybrid solar cells have been fabricated using size-quantized PbS nanoparticles and poly (3-hexylthiophene) (P3HT). PbS was used as an electron-tran sporting layer whereas P3HT was used for hole transport. A photovoltaic device consisting of PbS and P3HT exhibited 3% incident photon to current efficiencies (IPCE) under 550-nm monochromatic irradiation. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: hybrid solar cells; PbS nanocrystals; inorganic semiconductor nanocrystals; STRONG QUANTUM CONFINEMENT; LIGHT-EMITTING-DIODES; STIMULATED-EMISSION; NANOCRYSTALS; POLYMER; DOTS; Energy & Fuels; Materials Science; Physics